Food supply and security - Reddy, Anugu Amarender; Babu, Suresh Chandra; Kumar, Parmod; Kumar, Soora Naresh (Springer, 2023)
India’s total food grain production in 1950–1951 was low at 50.8 million tonnes, with a population of 361 million. Thus, the food grain production in 1950–1951 was 140.7 kg per person per annum or 0.39 kg per day. Thanks to Indian farmers and agricultural scientists who worked hard to increase the food grain production through new crop varieties and production technologies, along with the supportive policies of the governments that paved the way for the Green Revolution in Indian Agriculture. Achievements of the green revolution further led to achievements in other agricultural and allied sectors like the white revolution with substantial gains from milk production, followed by the yellow revolution with a significant increase in edible oilseed production, and the pink revolution with an increase in meat and poultry production to a significant extent. This chapter mainly discusses where does India stand today in terms of its agriculture when compared to its independence in 1947? As the data for 1947 for most of the indicators is not available, 1951 is considered the base year and compared the various indicators for the year 2021.